Development of Training on Writing Digital Textbooks Based in On in Service Learning for Teacher - Hidayah, Ratih; Prihatin, Titi; Utanto, Yuli (Universitas Negeri Semarang, 2021)
Efforts to improve the quality of education include various training to improve teacher competence, for example by writing books, popular articles, and journals. Therefore, schools must pay attention to the performance of teachers with all their energy and capital to improve these skills. This study aims to develop a digital textbook writing training model and also see an increase in teacher competence in textbook writing skills. The research is a development method. The object of research is the teacher who participates in textbook writing training, research instruments in the form of questionnaires and interviews. Use Regression method analysis. The results showed that from several training models, it was the in-on-in service-learning training model that influenced increasing teacher competence in making textbooks. These findings confirm that the in-on-in service-learning model can improve teacher competence in writing digital textbooks